Identification of late intrauterine growth restriction with normal umbilical Doppler using multiparameter diagnostic algorithm in the Maternal Perinatal National Institute - admin, admin (2018)
Objectives. To identify late intrauterine growth restricted newborns (IUGR) with normal umbilical artery Doppler and assess the antepartum diagnostic value of a multi parameter algorithm. Material and methods. Analytic, observational, retrospective study and elaboration plus preliminary assessment of a diagnostic tool. 96 non anomalous newborns between 35 and 41 weeks of gestational age were randomly selected. 23 small for gestational age (SGE) according to local growth classification method, 13 borderline adequate for gestational age (AGE)(inside the 200 g over tenth percentile ) and 60 AEG over the 25 percentil. Using a pre established operative definition 22 IUGR (cases) and 74 non IUGR (controls ) were detected. For Statistical analysis we used Epidat 3,1 to calculate values for simple diagnostic Tests. Results. 22 from 96 (23% ) newborns were classified as IUGR; 16 from 23 (69,5 %) SGE , 6 from 13 (46,2% ) borderline AGE and 0 from AGE over the 25 percentile. Global Sensitivity, Especificity, PPV, NPV, PC + and CP – were 86,4%; 95,9%; 86,4%; 95,9%; 21,3 and 0,14, respectively. Only 4 from 22 (18%) cases of IUGR were diagnosed as such in the antepartum unlike 19 from 22 (86.4%) using the diagnostic algorithm. Conclusions. The use of the multi parameter diagnostic algorithm improves the identification of late IUGR fetus with normal umbilical artery Doppler.